Social media and political engagement: a study of Malaysian youth in the 15th general election - Yahaya, Fatimah Yazmin; Adnan, Wardatul Hayat; Hassan, Mohd. Sufiean (Faculty of Communication & Media Studies, 2025)
This study explores the impact of social media on political engagement among youth in Selangor. Utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model, the study investigates how performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, and habit influence youth's intentions to use social media for political purposes. Key findings highlight that performance expectancy and social influence are significant predictors of political engagement, while facilitating conditions also play a crucial role. Hedonic motivation and effort expectancy show moderate influence, whereas habitual use of social media does not significantly impact political engagement. The study underscores the importance of perceived usefulness, peer influence, and access to technology in shaping political behavior. These insights are valuable for policymakers, educators, and campaigners aiming to enhance youth political engagement through social media. Future research should further explore the nuanced roles of hedonic motivation and effort expectancy to develop targeted strategies for fostering political engagement among youth.